COMPARISON OF VEHICLE HANDLING MODELS (Perner's Contacts, 2015)
Vehicle handling quality is one of the most significant factor of the active road safety. This paper proposes and compares four variants of computational models usable for the vehicle handling analysis. The first three of them are based on single track model extended by Magic Formula tire model and lateral load transfer during cornering. The last one is a multi-body model created in MSC Admas software which is a three-dimensional model of the vehicle comprised of individual subsystems with many degrees of freedom. Presented models are validated with measurement of double lane change manoeuvre executed by the Formula Ford car.